2006
DOI: 10.1101/gr.5094806
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phylogenetic analyses reveal mammalian-like clockwork in the honey bee (Apis mellifera) and shed new light on the molecular evolution of the circadian clock

Abstract: The circadian clock of the honey bee is implicated in ecologically relevant complex behaviors. These include time sensing, time-compensated sun-compass navigation, and social behaviors such as coordination of activity, dance language communication, and division of labor. The molecular underpinnings of the bee circadian clock are largely unknown. We show that clock gene structure and expression pattern in the honey bee are more similar to the mouse than to Drosophila. The honey bee genome does not encode an ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
270
1
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(316 citation statements)
references
References 117 publications
28
270
1
11
Order By: Relevance
“…1 B, C). We further analyzed brain transcript levels for Cry and Per, which are the clock genes that show the most robust oscillations in honey bees (Rubin et al, 2006;Shemesh et al, 2007). We found that both Cry and Per transcript levels oscillated with higher levels during the night in foragers, but not in nurses, which is consistent with previous analyses of honey bees (Toma et al, 2000;Bloch et al, , 2004Shemesh et al, 2007) (Fig.…”
Section: Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…1 B, C). We further analyzed brain transcript levels for Cry and Per, which are the clock genes that show the most robust oscillations in honey bees (Rubin et al, 2006;Shemesh et al, 2007). We found that both Cry and Per transcript levels oscillated with higher levels during the night in foragers, but not in nurses, which is consistent with previous analyses of honey bees (Toma et al, 2000;Bloch et al, , 2004Shemesh et al, 2007) (Fig.…”
Section: Methodssupporting
confidence: 78%
“…6 A). Cosine models typically account for much of the variation in transcript levels during the day for genes that are regulated by the circadian clock (Rubin et al, 2006;Krupp et al, 2008). We normalized the obtained amplitude and R 2 for each group relative to those in nurse bees from the same colony and experiment (e.g., the normalized value is 1 if the amplitude for the nurse age bees is similar to that of nurse bees from the same colony).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations